The Influence of Supply Chain Strategy on Employee Performance on Small and Medium Business in Beringharjo Market, Yogyakarta- Indonesia - Sunarsi, Denok (ExcelingTech, 2020)
Abstract- This study aims to look at supply chain strategy with job satisfaction as an intervening variable at SMB in Beringharjo market, Yogyakarta. This study is used a descriptive verification approach and is analyzed using SEM technique in AMOS version 21. The research sample were 218 employees in SMB in Beringharjo Market and the primary data were obtained from questioners; while secondary data was obtained through notes, publications and literature. The results showed supply chain strategy has a positive and significant effect on performance and satisfaction; and satisfaction has a positive effect on performance through satisfaction mediation. This study is proposed to find out supply chain strategy aspects related to employee performance at SMB in Beringharjo market and also emphasize aspects of supply chain strategy that have an impact on performance, especially on SMBs and the results of the research are expected to enrich the management literature, especially in the Human Resource field.